Evaluasi Program Terapi Al-Quran Melalui Model Context, Input, Process, Product (CIPP) - Made Dike Julianitakasih Ilyasa; Abd. Madjid (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
The purpose of this study is to evaluate the aspects of Context, Input, Process, and Product of the Al-Qur'an Therapy Program at Sekolah Khusus Taruna Al-Quran. This research uses a qualitative approach with a descriptive analytic type. The data collection techniques are non-participant observation, interviews, and documentation. The data analysis was performed through data reduction, data presentation, and conclusion drawing. The results show that: 1) The background of the implementation of the Al-Qur'an Therapy Program at Sekolah Khusus Taruna Al-Quran is the existence of the students with special needs at Taruna Al-Qur'an Kindergarten which is a regular Kindergarten (Context aspect), 2) The Human Resources (HR) for the Al-Qur'an Therapy Program consists of mentors, namely devotion students from Pondok Pesantren (Islamic Boarding School) Al-Qur'an Taruna and companions, namely teachers who accompany each student (Input aspect), 3) The Implementation of the Al-Quran Therapy Program is started with an opening greeting by the teacher, followed by greeting the students, reciting theraupetic verses by both the teacher and the student which is stated by reciting ta'awu?, and the teacher dismiss the therapy session by giving a closing greeting (Process aspect), 4) The students who join the Al-Quran Therapy Program tends to be calmer and they even can memorize and recite the verses of Al-Quran (Product aspect).